The Economic Benefits of Organised Banking Tawarruq - Amhammed, El-chanee; Talbi, Salaheddine (Finance and Business Economies Review, 2020)
The financing process plays an important role in the economy by financing various investment operations to achieve economic development, and in this regard, Islamic finance differs from traditional financing because of Islamic finance is based on the principles of Islamic Shariah. This study examines the economic benefits of organized banking tawarruq as one of the Islamic financing formulas approved by many Islamic banks, as it is considered one of the different issues in their application with banks, due to the difference in For legal fatwas, and Islamic banks that have approved it and use it as a financing tool to meet the needs of customers. Organized banking tawarruq has witnessed a major shift in Sharia contracts in many countries, as it contributed to the development of banking activity with contracts directly related to the development of production activity.